Metabolomic and Transcriptomic Analysis of Flavonoid Biosynthesis in Two Main Cultivars of Actinidia arguta Sieb.Zucc. Grown in Northern China - Wang, Yubo; Wang, Yong; Sun, Jun; Dai, Yue; Yang, Fengyan; Jiang, Hui; Irfan, Muhammad; Chen, Lijing (Frontiers in Plant Science, 2022)
Actinidia arguta Sieb.Zucc. is a fruit that is rich in flavonoids. Nevertheless, details of flavonoid formation and the potential mechanism behind flavonoid biosynthesis have not previously been reported. In order to explore the biosynthetic regulation mechanism of flavonoids in A. arguta Sieb.Zucc., we conducted a combination of extensive targeted metabolite analysis and analyzed transcriptomes to determine the flavonoids present and the genes bound up with flavonoid biosynthesis in the two main cultivated varieties of A. arguta Sieb.Zucc. in Northern China. The maturity period is from August to September. A total of 118 flavonoids were found in fruits. Among them, 39 flavonoids were accumulated at significant levels after fruit ripening. Transcriptome analysis indicated that most flavonoid biosynthesis structural genes and certain regulatory genes exhibited differential expression between the two varieties. Correlation analysis of transcriptome and metabolite profiles showed that the ways of expression of 21 differentially expressed genes related to structure and regulation between the 2 varieties were more highly correlated with 7 flavonoids after fruit ripening. These results contribute to the development of A. arguta Sieb.Zucc. as a food and drug homologous functional food.